Hydrocracking of pyrolyzed α-cellulose to hydrocarbon over MxOy/Mesoporous carbon catalyst (M = Co and Mo): Synthesis and characterization of carbon-based catalyst support from saw waste of Merbau wood. Issue 3 (June 2020) - Santi, Darma; Triyono,; Trisunaryanti, Wega; Izul Falah, Iip
Highlights: Mesopore carbon preparation via single-step carbonization-oxidation. Mesopore carbon from saw waste of Merbau wood as potential catalyst support. The catalyst Co/MC72 and Mo/MC72 selective for the hydrocarbon compounds. Abstract: Single-step synthesis of mesopore carbon (MC) was synthesized via carbonization and oxidation of saw waste of Merbau wood (Intsia, spp). MC as support Mx Oy (M = Co, and Mo, x and y represent the type of metal oxide formed) were synthesized and introduced to the hydrocracking of pyrolyzed α-cellulose (bio-oil). The MC samples were characterized by XRD, FT IR, total acids groups obtained titrimetry by Boehm method, SEM, and Surface Area Analyzer (SAA). The two highest specific surface area of the MC, which was carbonized at 800 °C for 3 h (MC83) and at 700 °C for 2 h (MC72), were 350.56 m 2 /g and 330.31 m 2 /g, respectively. The MC72 showed the highest average pore diameter of 2.758 nm. The MC72 was then used as a support of cobalt and molybdenum metal (Co/MC72 and Mo/MC72) as a catalyst hydrocracking of bio-oil. The SAA results showed that the specific surface area of Co/MC72 has increased to 384.7 m 2 /g and of Mo/MC72 has decreased to 25.43 m 2 /g. The results showed the Co/MC72 and Mo/MC72 catalyst improved the quantity (as conversion 75.33 and 74.69 wt.%, respectively) and quality of bio-oil (as selectivity toward hydrocarbon compound of alkanes by Co/MC72 and Mo/MC72, moreover the alkenes by Co/MC72). The liquid product consisted of C2 -C6 of aldehydes, ketones, acids, alcohols, furans, phenols, and hydrocarbons. The hydrocarbon compounds contained propane (11.56 wt%), 2-deutero-2-methyl propane (24.90 wt.%) and 4-methyl-1-pentene (1.11 wt%).